«That is what our job is. We light the flame»: An interview with Valerie Fisher, a Canadian elementary teacher at R. Gordon Sinclair Memorial School, Kingston, Ontario (Foro de Educacion, 2016)
Valerie Fisher is an experienced elementary school teacher with specialized training in music. She has been teaching in elementary education in Canada for more than 30 years. In learning about her professional background, we will travel across the country, from Nova Scotia to Alberta and finally to Ontario. In the country of Canada, education is under provincial jurisdiction. Teaching in three provinces has given Mrs. Fisher a colourful taste of this diverse and broad country. Last 25th March I had the opportunity to spend one day in a Canadian school with Valerie Fisher, in her classroom at R. Gordon Sinclair Memorial School, located in Kingston (Ontario). She has a «split grade» class, which means that she teaches grade 1 (6-7 years old) and 2 (7-8 years old) together. Read More. . .